Effect of Swim-Up and Percoll Treatment on Sperm Quality and In vitro Embryo Development in Yak - Ben LIU; Yan CUI; Si-jiu YU (Journal of Integrative Agriculture, 2013)
This study was designed to determine the effect of different sperm preparation treatments on yak sperm quality and in vitro embryo development. Frozen-thawed semen samples were treated using swim-up or percoll gradient centrifugation methods. Sperm concentration, progressive motility, recovery of motile sperm, membrane integrity, acrosome and chromatin integrity were scored and compared in recovered samples and controls. In addition, the effects of two sperm separation treatments on embryos capable of cleavage and in vitro development to the blastocyst stage were evaluated. Swim-up separated sperm showed a higher motility, while the concentration of spermatozoa recovered and percent recovery of motile sperm were higher with percoll gradient centrifugation separation. According to the optical and electron microscopies, swim-up produced higher percentage of sperm with intact plasma membrane and acrosome than percoll gradient centrifugation separation. However, there was no difference in the percentage of sperm with intact chromatin between two treatment groups. Cell numbers in the blastocysts of two groups were not different. The blastocyst rate was similar in both groups, whereas cleavage rate was higher when swim-up was used.